Frequency, Predictors, and Outcome of Seizures in Patients With Myelomeningocele: Single-Center Retrospective Cohort Study. (January 2022) - Karakas, Cemal; Fidan, Emin; Arya, Kapil; Webber, Troy; Cracco, Joan B.
To determine the frequency, predictors, and outcomes of seizures in patients with myelomeningocele, we retrospectively analyzed the data from patients with myelomeningocele followed longitudinally at a single center from 1975 to 2013. We identified a total of 122 patients (61% female). The mean follow-up duration was 11.1 years (minimum-maximum = 0-34.5 years, SD = 8.8, median = 9.1 years). A total of 108 (88.5%) patients had hydrocephalus, and 98 (90.7%) of those patients required a ventriculoperitoneal shunt procedure. Twenty-four (19.7%) patients manifested with seizures, 23 of whom had hydrocephalus. The average age of seizure onset was 4.8 years (median 2 years of age). Falx dysgenesis ( P = .004), lumbar myelomeningocele ( P = .007), and cortical atrophy ( P = .028) were significantly associated with epileptic seizure development. The average seizure-free period at the last follow-up in patients with a history of myelomeningocele and seizures was 8.1 years. We conclude that myelomeningocele patients with seizures have an overall good prognosis with considerable long-term seizure freedom.